(untitled) (Coordinates of Public Administration, 2026)
The article provides a comprehensive review of current trends in the implementation of the concept of strategic investment management in public authorities of Ukraine. Particular attention is paid to the analysis of institutional, regulatory, and organizational and economic prerequisites for the effective implementation of strategic investment management in the context of transformational changes and post-war recovery. Key challenges that hinder the implementation of this policy are identified, namely, insufficient coordination between levels of government, limited financial resources, and imperfect mechanisms for assessing the effectiveness of investment projects. The relevance of the study is due to the growing role of strategic investments in ensuring sustainable socio-economic development of Ukraine in the context of deep transformations associated with European integration processes, military challenges, and the need for post-war recovery. The current stage of the state's development is characterized by the need for significant amounts of investment resources aimed at rebuilding infrastructure, modernizing key sectors of the economy, and increasing the competitiveness of the national economy. In the context of European integration, the issue of ensuring investment security, improving state regulation mechanisms, and creating a favorable investment climate is of particular importance, which involves increasing the level of legal protection for investors and developing public-private partnerships. The implementation of reforms in the field of public investments also requires harmonizing strategic documents with the real needs of territorial communities and development priorities, which emphasizes the need to implement a systemic and strategic approach to investment management.